Changes in maternal body composition during pregnancy. (18th April 2012) - O'Dwyer, V; Hogan, J; Farah, N; Kennelly, MM; Stuart, B; Turner, MJ
Abstract : Introduction: Concerns about maternal obesity have led to new American recommendations on gestational weight gain (GWG). However, there are few prospective longitudinal studies on GWG and changes in maternal body composition as pregnancy advances. This study analysed maternal body composition changes during pregnancy and the puerperium. Methods: Women were enrolled at their convenience in the first trimester. Weight and height were measured and Body Mass Index calculated. Maternal body composition was measured using bioelectrical impedance analysis at 9-14 weeks, 16-21 weeks, 23-25 weeks, 28-30 weeks, 32-34 weeks, 37-40 weeks gestation and 12 weeks postpartum. Results: There were 101 women enrolled in our study. The mean GWG was 12.2 SD+/- 4.7 kg. GWG was associated with increases in fat and fat-free measurements. Over two thirds of gestational weight gain occurred before the third trimester of pregnancy. There was a greater increase in maternal fat measurements in the second trimester than in the third trimester. There was a greater increase in total body water measurements in the third trimester compared with the second trimester. Of the 74 women that attended at 12 weeks postpartum 7 women weighed less than at their first antenatal visit and the mean weight gain was 4.1 +/- 4.9 kg. More women were overweight or obese postpartum than at the first visit based on their BMI (n=42). Conclusion: Maternal body composition changes during pregnancy. GWG can be attributed to fat deposition, increased total body water, and intrauterine growth. These changes can affect overweight and obesity rates.